People, not technology, should drive innovation in elite sport - Buttfield, A.; Polglaze, T. (Sensoria - A journal of mind, brain and culture, 2016)
Innovations derived from technological advances and the associated potential competitive advantages are keenly sought within elite sport. However, successfully gaining a competitive advantage relies heavily on the coaches and sport scientists responsible for utilising and implementing any new technology. Establishing the accuracy of new technology or metrics, efficiently integrating new technology or innovative methods into existing practice, and ensuring that any new innovation is adding value to the service being provided without causing a distraction are all areas where the individual sport scientist or coach must lead the technological innovation rather than allowing the technology to lead them.